The immunoregulatory role of gut microbiota in the incidence, progression, and therapy of breast cancer - Xue, Kaiyang; Li, Jiawei; Huang, Ruijie (Frontiers in Cellular and Infection Microbiology, 2024)
Breast cancer (BrCa) is the most prevalent malignant tumor in women and one of the leading causes of female mortality. Its occurrence and progression are influenced by various factors, including genetics, environment, lifestyle, and hormones. In recent years, the gut microbiota has been identified as a significant factor affecting BrCa. The gut microbiota refers to the collective population of various microorganisms in the human gastrointestinal tract. Gut microbiota is closely associated with human health and disease development, participating in crucial physiological functions such as digestion, metabolism, immune response, and neural regulation. It has been found to influence the occurrence and treatment of BrCa through a variety of mechanisms. This article aims to review the immunomodulatory role of the gut microbiota in the development and treatment of BrCa.